IL-18 binding and inhibition of interferon γ induction by human poxvirus-encoded proteins - Xiang, Yan (The National Academy of Sciences, 1999)
Molluscum contagiosum virus (MCV) is a common, human poxvirus that causes small papular skin lesions that persist for long periods without signs of inflammation. Previous studies revealed that MCV encodes a family of proteins with homology to mammalian IL-18 binding proteins. IL-18 is a proinflammatory cytokine that induces synthesis of interferon γ, activates NK cells, and is required for a T-lymphocyte helper type 1 response. We expressed and purified the proteins encoded by the MC53L and MC54L genes of MCV, as well as their human and murine homologs. All four recombinant proteins were able to bind with high affinity to human and murine IL-18 molecules and inhibited IL-18 mediated interferon γ production in a dose-dependent manner. The pirating of IL-18 binding proteins by poxviruses and their use as decoy receptors is consistent with the critical role of IL-18 in defense against virus infections and provides a mechanism for evasion of the immune system by MCV.